Preradioactive Iodine Thyroglobulin Levels as Predictors of Metastasis in Well-Differentiated Thyroid Carcinoma Patients - Darmawan, Budi; Sari, Meutia; Susilo, Stefani; Kartamihardja, Achmad Hussein S. (World Journal of Nuclear Medicine, 2022)
Objective The aim of this study was to determine the cut-off value of thyroglobulin (Tg) levels as a predictor of metastases in post total thyroidectomy patients with well-differentiated thyroid carcinoma (DTC).Materials and Methods A retrospective case-control study with an observational diagnostic approach was done. Subjects were 102 DTC patients divided into a case group with metastases and a control group without metastases. Tg and antithyroglobulin antibody (ATA) levels on thyroid-stimulating hormone (TSH)-stimulated preradioactive iodine were compared with each other. Diagnosis of metastases was based on postradioactive iodine whole-body scan. The cut-off value for Tg preradioactive iodine and the area under the curve (AUC) were obtained from the receiver operating characteristic curve.Result The characteristics and histopathological type of DTC among these two groups were not significantly different (p = 0.47). The Tg levels in the case and control groups were 106 (2.2–6,000) ng/mL and 2.7 (0.3–10.10) ng/mL, respectively (p = 0.0001). TSH level in the case group was 50 (30–107) µIU/mL and in the control was 50 (20–100) µIU/mL (p = 0.224). ATA levels in the case and control groups were 0–3,000 and 0–629 ng/mL, respectively (p = 0.01). The AUC was 0.976 with a 95% confidence interval of 0.924 to 0.996 and a standard error of 0.016. The cut-off value of preradioactive iodine Tg was 10.1 ng/mL or higher with sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of 96.1, 100, 98.0, 100, and 96.2%, respectively.Conclusion Preradioactive iodine Tg level 10.1 ng/mL or higher can be used as a predictor of metastasis in patients with DTC.
Keywords: well-differentiated thyroid carcinoma; metastasis; thyroglobulin